The Impact of Public Transport Network Accessibility on Trip Generation Model - Krasić, Davor; Novačko, Luka (Promet - Traffic&Transportation, 2015)
The most commonly used model in transport planning is the four-step model of transport demand. Although a number of improvements have been made to this model over the past six decades of use, its main weakness remains that the characteristics of the transport network are not included in the sub-model of trip generation. In the research presented in this paper the authors investigated the possibility of improving this key model. Based on the results of correlation and regression analysis it has been proven that the public transport network accessibility significantly affects the total number of generated trips. This opens up new possibilities for improving this model as well as the process of transport planning.